DIAGNOSIS OF LEARNING DIFFICULTIES IN MATHEMATICS (GEOMETRY) FOR STUDENTS GRADE X AT SMK NEGERI 3 YOGYAKARTA - Shella Azizah; Sahid . (Universitas Negeri Yogyakarta, 2017)
The objectives of this research are to describe the difficulties of students and their causes in solving geometry problems. The difficulties were observed related to the concept and principles.This research is a qualitative research with case study strategy. Subjects of this research are seven students of class X KR 1 and X TP 2 at SMK Negeri 3 Yogyakarta whom diagnosed have learning difficulties in solving geometry problems. Qualitative data were collected by test and interviews. The data were analyzed descriptively qualitative.The results show the concept of geometry that has not understood by students are the concept of solid geometry (cubes and rectangular prism), right triangle, the projection (the point on the line, the point on the plane, and the line on the plane), perpendicular concept (two lines, lines and plane), distance (point to the line, point to the plane and two parallel planes), and angle (lines and plane, two planes). Meanwhile, the principle of which is not mastered by students are the principle of projection, distance calculations, the Pythagorean theorem, calculation of the root, the calculation of the angle and trigonometry comparison. The cause of the learning difficulties by students is students do not have awareness to learn regularly.